Germany in our time : - Grosser, Alfred (Pall Mall Press, 1970)
Supporting these themes throughout, Alfred Grosser is nonetheless sensitive to continuities from the past. In an introductory chapter that is as remarkable for its compression of the salient information about Germany's past as for its balanced analysis of the prewar period, Professor Grosser highlights those elements in German society and politics that have indeed carried over through the Occupation and into the present day.